Effectiveness of some biorationals in controlling damping-off diseases and promoting growth and yield of wheat crop - Neima, Hemin Abubakir; Mustafa, Rebwar Ahmed; Ali , Sawsan Mohammed; Fatah, Nazhad Majeed; Rahim, Bayan Rashid (Journal of Kerbala for Agricultural Sciences, 2022)
This study aimed to evaluate the effectiveness of treating wheat seeds with some indigenous medicinal plants powder on the germination rate, growth and yield of wheat, as well as, a commercial fungicide (Tebuconazole) and a bio growth promoter Bacillus subtilis bacteria+ amino acid were applied for the same purpose. The results of this study indicated that seed coated with Chamomile flower powder (T1) suppressed damping-off by 89.22% compared with 0% in control and gave a significantly higher number of tillers (6.583 ± 0.617) compared to T0 and other treatments. Meanwhile, the T1 gave the highest plant heights, straw, and total shoot dry mass (94.0± 1.684, 9.096 ± 1.154, and 10.192 ± 1.216), respectively. in the meantime, T1 significantly provided the uppermost number of spikes, spike length, and yield (6.083 ± 0.594 spike/plant, and 3.380±0.017 ton.ha-1), respectively. On the other hand, T4 treatment performed a significantly higher weight of spikes and grains per spike (1.521 ± 0.092 and 1.065 ± 0.068), respectively. Furthermore, T4 conferred a higher number of grains per spike (33.431 ± 1.915) than other treatments. The yield in all the treatments was significantly higher than in the control (p-value ≤ 0.05), and the highest yield was recorded in the T1 (mean =3.380±0.017).